PROVISION OF SUPPLEMENTARY FOOD FOR SASIGO AND BISCUIT IN INCREASING THE WEIGHT OF CHILDREN : A COMPARATIVE STUDY IN NAMBO PRIMARY HEALTH CARE IN KENDARI CITY: SASIGO AND BISCUIT AND CHILDREN WEIGHT - Mariyatni Rasyid; Timbul Supodo; La Banudi (STIKes Mandala Waluya Kendari, 2021)
Background: The prevalence of community nutritional status in the Kendari City area in 2016 was 0.23%, decreased in 2017 by 0.13%, increased in 2018 by 4.67% and decreased by 2.25% in 2019 Although the prevalence rate of nutrition tends to decrease, although not significantly, the problem is nutritional status there are still many in the Kendari City Area. Thus, Kendari City shows that children under five have not reached the target of nutritional status, where the current nutritional status of children under five is 0.21% while the Minimum Service Standard (SPM) is 8.1%. Methods:The type of research in this research is pre-experimental research with a Pre Test - Post Test design. This research was conducted in the working area of ??Puskesmas Nambo, Kendari City. Population of 227and a sample of 67 malnourished toddlers in 2019. Result:Based on the independent sample test output in the Equal Variances Assumed section on Local PMT (Bagea Sasigo), it is known that the sig (2-tailed) value is 0.001 <0.05, so Ha is accepted so that there is a significant difference between the provision of local PMT (Bagea Sasigo). Whereas in the Government PMT (biscuits) it is known that the sig (2-tailed) value is 0.000 <0.05, so Ha is accepted so that there is a significant difference between the provision of government PMT (biscuits) to toddlers in the Work Area of ??the Puskesmas Nambo, Kendari City. Conclusion:Provision of Local PMT (Bagea Sasigo) and Government PMT (Biscuits) for toddlers Before giving the intervention it was not effective while after giving the intervention it was effective and significant.